ЖЫРАЎ-ШАЙЫРЛАР ДӨРЕТИЎШИЛИГИНДЕ СӨЗ-ЖЫР ИМПРОВИЗАЦИЯСЫ - Матимов, К.Г. (FAN va JAMIYAT, 2020)
The article discusses the issue of improvisation in Karakalpak literature in the works of the ancient poet Soppasli Sipira, Asan Kaygi, Dospambet, Muyten and others. And also, it is said about the occurrence of the phenomenon of improvisation, the stages of the formation of the Karakalpak folklore, that it originates from the legacy of poets-jirau of the early period and continues in today’s Karakalpak literature, and in modern folklore, including traditional songs.